Expert-probabilistic prognostication of production process qualitative index of radiation bioengineering recorders - Лавриненко, Сергей Николаевич; Запорожченко, Елена Евгеньевна; Сазонова, Марина Сергеевна; Лавриненко, Олег Сергеевич (Technology audit and production reserves, 2015)
Extension of the fields of application and increasing the content of radioactive isotopes in the biosphere, as well as changes in their qualitative composition, increase the risk of radioactive contamination of the human environment and have an adverse impact on life processes. Extremely important the pollution control of environment by radioactive substances in the general system of nature protection and development of high-quality technical resources for its implementation. The main elements of dosimetry equipment and other means of measuring ionizing radiation in nuclear power engineering and biomedicine, with which this control is carried out, are detectors that generate certain signals, which detect and characterize parameters of ionizing radiation. The sensitivity of the measurements, as well as most of the accuracy characteristics of the detectors to a large extent depend on the excellence of their design, quality manufacturing and operating modes. Therefore, the use of Bayesian methods is an urgent task for classification, regression forecasting and recovery required for operating of probabilistic characteristics of quality assurance in the actual processes of production. The article discusses aspects of the application of Bayes’ theorem on the conditional probability of certain events for a given probability of another event to address improving quality indicators in the production of bioengineered destination and particularly recorders of ionizing radiation.